The Effect Of Work Motivation And Work Ability On Employee Performance At Pt. Tiga Putri Bersaudara Site (Location) Wsl - Azrol Hafiz AN; Nidyawati Nidyawati; Heri Fitriadi (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
The purpose of this study was to determine the influence of work motivation and work ability on employee performance at PT. Tiga Putri Bersaudara Site WSL. The results of the study showed that (1) work motivation has a significant partial effect on performance, as evidenced by the calculated t value > t table (7.417 > 1.990). (2) work ability has a significant partial effect on performance, as evidenced by the calculated t value > t table (3.087 > 1.990). (3) work motivation and work ability have a significant simultaneous effect on performance, as evidenced by the calculated f value > f table (63.065 > 3.959), with a significance value lower than the significance level (a) of 0.05 (0.000 < 0.05).